Peri-Urban Area of Bogor: Identification of Physical, Social, and Economic Characteristics - Janthy Trilusianthy Hidayat; Mujio, Mujio; Lesmana, Raka Al-Farithsi (Jurnal Ar Ro'is Mandalika (Armada), 2025)
Peri-Urban Area (WPU) is an area located between areas that have an urban appearance on one side and a rural appearance on the other (Yunus, 2008). The Bogor Regency WPU which borders Bogor City is developing dynamically and may at any time be uncontrollable. In this research, three analytical techniques were used. First, it was carried out using GIS overlay analysis to determine the urban or rural characteristics of the Bogor Regency WPU. Second, it is carried out using scoring analysis to determine the score results for each predetermined variable. Then you will get the total score for each variable. Thus, a typology of Bogor Regency WPU was obtained based on its characteristics. The final analysis technique is descriptive qualitative to determine the appropriate direction for Bogor Regency WPU based on the characteristics, typology, and interactions of the Bogor Regency WPU community obtained through questionnaires. The results of the research show that of the 35 villages/sub- districts of Bogor Regency that border directly with Bogor City. 4 villages and 1 sub-district have a rural peri-urban typology with high rural characteristics and not too much interaction with Bogor City, while 25 have a secondary peri-urban typology with balanced rural and urban characteristics and moderate interaction